An Open-Label Trial of Memantine for Cognitive Impairment in Patients with Posttraumatic Stress Disorder. (12th May 2015) - Ramaswamy, Sriram; Madabushi, Jayakrishna; Hunziker, John; Bhatia, Subhash C.; Petty, Frederick
Abstract : Background . Studies using standard neuropsychological instruments have demonstrated memory deficits in patients with PTSD. We evaluated the efficacy and safety of the N-methyl-D-aspartate antagonist memantine in veterans with PTSD and cognitive impairment. Methods . Twenty-six veterans with PTSD and cognitive impairment received 16 weeks of memantine in an open-label fashion. Cognition was assessed using the Spatial Span, Logical Memory I, and Letter-Number Sequencing subtests of the Wechsler Memory Scale III and the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS). RBANS measures attention, language, visuospatial skills, and immediate and delayed memories. The Clinician Administered PTSD Scale (CAPS), Hamilton Depression Scale (HAM-D), Hamilton Anxiety Scale (HAM-A), Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q), and Sheehan Disability Scale (SDS) were secondary outcome measures. Results . There was a significant improvement in RBANS, both total and subscale scores (P < 0.05 ), over time. There was a reduction in total CAPS scores, avoidance/numbing symptoms (CAPS-C) and hyperarousal symptoms (CAPS-D), HAM-D, Q-LES-Q, and SDS scores. However, there was no reduction in reexperiencing (CAPS-B) and HAM-A scores. Memantine was well tolerated. Conclusions. Memantine improved cognitive symptoms, PTSD symptoms, and mood in veterans with PTSD. Randomized double-blind studies are needed to validate these preliminary observations.